Dimeric and Trimeric Hydrolyzable Tannins from Quercus coccifera and Quercus suber (Journal of Natural Products, 2002)
Three new hydrolyzable tannins, cocciferins D1 (1), D2 (2), and T1 (4), were isolated from the leaves of Quercus coccifera. Cocciferin D2 (2) and two additional new tannins, cocciferins D3 (3) and T2 (5), were also obtained from the leaves of Quercus suber. Their oligomeric structures were elucidated on the basis of spectroscopic methods and chemical evidence. Compounds 2, 3, and 5 were rare oligomers possessing glucose cores with both open-chain and pyranose forms.
doi: 10.1021/np010465i